2014
DOI: 10.1108/jsocm-02-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Fighting to eat healthfully: measurements of the military food environment

Abstract: Acknowledgments (if applicable): This study was not funded by any external research partner. Study design, data collection, analysis, interpretation of data, and the decision to submit the paper for publication were the authors' own decisions. The authors acknowledge Dr Joy Parkinson and Dr Justin Fidock for suggestions and assistance provided during analysis and with early drafts of the manuscript. Finally acknowledgement and gratitude go to Kate Flinders for data collection, subsequent data entry and for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
(67 reference statements)
2
28
0
Order By: Relevance
“…Data from Australian studies of the consumer food environment were used for this analysis (22,23) , representing four suburban areas in Brisbane, Australia: one area with high SES (socioeconomic status) area 2km from the city; one medium SES area 6km from city; one low SES area 13km from 108 city and a further low SES area 50km from city (24) . The first two suburbs were less culturally diverse (70-80% Australian by birth, with 50-60% both parents Australian by birth) than second 110 two suburbs (50-65%% Australian by birth, with 25-40% both parents Australian by birth).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Australian studies of the consumer food environment were used for this analysis (22,23) , representing four suburban areas in Brisbane, Australia: one area with high SES (socioeconomic status) area 2km from the city; one medium SES area 6km from city; one low SES area 13km from 108 city and a further low SES area 50km from city (24) . The first two suburbs were less culturally diverse (70-80% Australian by birth, with 50-60% both parents Australian by birth) than second 110 two suburbs (50-65%% Australian by birth, with 25-40% both parents Australian by birth).…”
Section: Data Collectionmentioning
confidence: 99%
“…The resulting short-forms were then validated against long-90 form NEMS instruments with 193 outlets producing comparable results and a sizeable reduction 91 in time taken to administer the instrument noted (21) . This paper reports the results of a comparison between scores obtained using the longer versions of NEMS (19,20) and the short-form versions (21) , on an Australian sample of food outlets (22,23) . The aim was to critically examine whether important aspects of the food environment known to influence eating behaviour were captured by each instrument, therefore reflecting on the capacity of each tool to assess the healthfulness of the consumer food environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the review, there were not specific tools reported. In contrast, the literature about institutional foodservices refers to the "Nutrition Environments Survey" (NEMRS) as a valid checklist to evaluate healthy eating promotion [36][37][38][39] . Nevertheless, that survey has different versions, and one of them already is used in restaurants 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The radiuses were plotted using geographical information system (GIS) software, and the population of outlets was compiled [38] by physically traveling the area. Sample size calculations indicated that 25 outlets were needed in each group (low- and high-SES) to detect a significant ( p = 0.05) difference in a NEMS score of 5 points (80% power; SD = 6.2 points based on a previous Australian study [39]).…”
Section: Methodsmentioning
confidence: 99%